Pendampingan Peningkatan Nilai Guna Barang terhadap Akuntabilitas Infak di Masjid Desa Kwangsan, Karanganyar - Sulistyowati Sulistyowati; Lailla Hidayatul Amin; Januar Cahyo Wicaksono; Shofiyah Abidatul Mardiyah; Fitri Handayani (LPMP Imperium, 2024)
The focus of empowerment in community service activities is oriented towards non-profit organizations which are one type of public sector organization. In the implementation of community service carried out, the assisted subjects chosen were the administrators (takmir) of the mosque in Kwangsan Village, Jumapolo District, Karanganyar Regency. The assisted subject was chosen because he saw the condition of managing the source of funds for the mosque in the village was considered massively lacking. This has an impact on the condition of the mosque which becomes poorly maintained. In this report, community service activities are carried out in Kwangsan Village, Jumapolo District, Karanganyar Regency. Community service activities were attended by approximately 25 participants in each session. In this activity, an explanation was given about increasing the use value of goods and the concept of accountability. All participants already understood the material presented. The results of the assistance were carried out optimally. There is also an increase in infaq and funding sources of mosques in Kwangsan Village.